Adat Perkawinan Masyarakat Di Kabupaten Kepulauan Sangihe - Derek, Jumiani (Universitas Pendidikan Indonesia, 2019)
As a system, custom is very important for regulating marriage in every community. Contradictory cases, blood-related marital cases are categorized as acts of gross violations because they deviate from the traditional principles custom marriage of Sangihe, so that the perpetrators of such violations must be given appropriate sanctions. But nowadays along with the development, there is an assumption that custom is not in line with religious and is contrary to human rights, even though the community generally believes that the values contained in the marriage tradition are full of meaning and ritual to get God's grace and away from disaster and danger. Majelis Tua-Tua Kampung as an institution and implementing custom must be increasingly empowered so that customary preservation can be done well. The research process was carried out in Sangihe Island, North Sulawesi. This study used a qualitative method with research subjects selected based on the snowball sampling technique. Data collection techniques with observation, semi-structured interviews and documentation. While the data analysis technique is carried out by steps of reduction, presentation and verification. The result of the study show that: (1). Marriage custom is still functional in the Sangihe community, because until now the community is still carrying out customary marriages by undergoing several ropes, Dumalengu Wera, Menuleng Bera, Me Kahiang and Mengosa. These 5 stages are the manifestations of the values carried out by the Sangihe people from generation to generation for awareness and mutual agreement. (2). The costumary institution is still functioning, because the community always involves Majelis Tua-Tua Kampung members as a companion and as a speaker in the traditional marriage process. In addition, they also often take action by going around the village at night as an effort to prevent customary violations.